Multiple enterovirus genotypes circulating in children hospitalized with acute gastroenteritis in Thailand - Kattareeya Kumthip (2018)
© 2017 Elsevier B.V. Enterovirus (EV) infection is widespread and can lead to a broad range of clinical symptoms, from mild to severe forms of disease. EVs are not always classified as pathogen and the epidemiological surveillance of EV infection in acute gastroenteritis cases in Thailand remains unexplored. This study aims to investigate the frequency, seasonality and molecular characteristics of EV circulating in children hospitalized with acute gastroenteritis in Chiang Mai, Thailand from 2010 to 2014. A total of 1266 fecal samples were included in this study. RT-PCR amplification of the 5′UTR was used for EV screening and phylogenetic analysis of the VP1 sequence was performed for EV genotyping. EV was detected in 5.8% of infections (73 out of 1266). Based on VP1 sequence analysis, over half (50.8%) of the identified EV cases were caused by species C, and the next two most frequent were species B and A (35.4% and 13.8%, respectively). This study identified 28 different EV genotypes, EV-C96 and coxsackievirus A24 were the most frequent genotype detected (12.3% each). EV was detected throughout the year with an increase of detection rate in December–January and May–June. In conclusion, this study reported the prevalence of EV infection with a wide variety of EV genotypes in children with acute diarrhea.